2012
DOI: 10.1080/14620316.2012.11512852
|View full text |Cite
|
Sign up to set email alerts
|

An overview of climate and crop yield in closed greenhouses

Abstract: The closed greenhouse is a recent innovation in the horticulture industry. Cooling by ventilation is replaced partly (in semi-closed greenhouses) or completely (in closed greenhouses) by mechanical cooling. Excess solar energy is collected and stored to be reused to heat the greenhouse. In temperate climates, this concept combines improved crop production with energy savings. This paper presents an overview of climate, crop growth and development, and crop yield in closed and semi-closed greenhouses. The techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 69 publications
1
53
0
2
Order By: Relevance
“…Humidity in a greenhouse affects the growth and yield of crops such as tomatoes (Bakker, 1991;Jolliet and Bailey, 1992;Jolliet et al, 1993). Consequently, modern greenhouses use both CO 2 application and humidification by the fogging system (de Gelder et al, 2012;Harel et al, 2014). Yasuba et al (2011) investigated temperature, CO 2 concentration, and vapor deficit in a greenhouse with CO 2 application and fogging, and reported the yield improvement of Japanese tomato cultivars under the environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Humidity in a greenhouse affects the growth and yield of crops such as tomatoes (Bakker, 1991;Jolliet and Bailey, 1992;Jolliet et al, 1993). Consequently, modern greenhouses use both CO 2 application and humidification by the fogging system (de Gelder et al, 2012;Harel et al, 2014). Yasuba et al (2011) investigated temperature, CO 2 concentration, and vapor deficit in a greenhouse with CO 2 application and fogging, and reported the yield improvement of Japanese tomato cultivars under the environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An exception to these results was found with respect to the accumulation of phenolics, which were also significantly increased in the late summer. It was demonstrated that a maximum increase in contents of lycopene (by 30 %), ß-carotene (by 40 %), phenolics (25 %), titratable acids (by 8 %) and soluble solids (by 15 %) greater CO 2 differences can occur when the greenhouse is operated completely closed (De Gelder et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Near-surface and deep geothermal-energy are also important alternative sources of energy for greenhouse heating, where the utilization of deep geothermal energy is not so prevalent in Germany (Lund, Freeston, & Boyd, 2005;Sanner, Karytsas, Mendrinos, & Rybach, 2003). Another source of energy is the solar energy, which can be collected in heated closed-greenhouses using cold water from soil layers (De Gelder, Dieleman, Bot, & Marcelis, 2012). After absorbing the excess heat in the greenhouse, the heat energy is stored in the aquifer, which can be reused in winter by means of a heat-pump (Bot, 2001).…”
Section: Introductionmentioning
confidence: 99%